Breakthrough of rice quality and market share in rice to rice processing business (A case study in rural rice milling business in Karawang, West Java). Issue 1 (July 2020) - Rachmat, R; Suismono,; Hadipernata, M; Daniardi, S; Nugraha, S
Abstract: Small Rice Mill (SRM) has an important role in rice business. Nevertheless however, low quality of milled rice and changing in consumers preferences cause SRM faces difficulty to maintain the role. Development of a business called Rice to Rice Processing (R2P) presents as a breakthrough rice business that will support their existence. This study aimed at analysing the feasibility of R2P business integrates SRM and market share in a business partnership pattern. The study was conducted in Karawang as a rice production centre. The qualitative method employed for analysis includes technical and partnership pattern with medium and big scale rice miller. The financial aspect used the quantitative method of Net Present Value, Net Benefit Cost Ratio and Switching Value to check their sensitivity. The results showed R2P business is a feasible for technological and financial aspects. Technology has evolved to produce various qualities (premium or medium). The switching value analysis showed that a decrease in product prices is sensitively influencing the financial feasibility. To strengthen cooperation that enhancing mutually beneficial relationship, R2P assists equipment investment in and buy raw material from SRM in the shape of brown rice in a rational agreed price.